2000
DOI: 10.1038/sj.ijo.0801424
|View full text |Cite
|
Sign up to set email alerts
|

Prandial glucose regulation with repaglinide: its clinical and lifestyle impact in a large cohort of patients with Type 2 diabetes

Abstract: OBJECTIVE: Prandial glucose regulation has the potential for achieving good metabolic control with a low risk of hypoglycaemia and increased¯exibility with regard to eating patterns. Comparative studies have suggested that the prandial glucose regulator repaglinide is at least equivalent to sulphonylureas in terms of ef®cacy, but incurs a lower risk of major hypoglycaemia. However, these trials employed ®xed dosing and mealtime regimens, so repaglinide was not used as intended. This prospective investigation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…We also found that repaglinide improves fasting (preprandial) glucose levels as well as HbA 1c levels despite only 4 weeks of treatment. The findings match those in other studies with repaglinide (27)(28)(29). The fact that the reduction in prandial glucose excursions induced by this short-acting compound also leads to a reduction in fasting glycemia clearly underlines the importance of controlling prandial glycemia.…”
Section: Figure 2-plasma Insulin and Blood Glucose Levels At Baselinesupporting
confidence: 80%
“…We also found that repaglinide improves fasting (preprandial) glucose levels as well as HbA 1c levels despite only 4 weeks of treatment. The findings match those in other studies with repaglinide (27)(28)(29). The fact that the reduction in prandial glucose excursions induced by this short-acting compound also leads to a reduction in fasting glycemia clearly underlines the importance of controlling prandial glycemia.…”
Section: Figure 2-plasma Insulin and Blood Glucose Levels At Baselinesupporting
confidence: 80%
“…2). These results are concordant with those of a recently completed open-label study involving a cohort of nearly 6,000 patients with type 2 diabetes that showed no weight gain associated with flexible prandial repaglinide in patients naive to antidiabetic drug therapy or switched from alternative antidiabetic agents (20). This study also showed that patients switched from sulfonylureas reduced their daily frequency of supplementary snacks.…”
supporting
confidence: 80%
“…In therapy-naive patients with diabetes mellitus, [83,[85][86][87] repagli-3.2 Renal Impairment/Failure nide reduced HbA1c, FPG, and PPG levels to the same extent as in controlled trials. None of these studies reported significant weight Several studies on repaglinide in patients with renal impairment gain in treated patients and the frequency of hypoglycemic epihave been published.…”
Section: Treatment-naive Patientsmentioning
confidence: 99%
“…As Ramadan is only of 4 weeks' duration, fructosamine instead of HbA1c has been used in most studies as the 2.5 Observational Studies (Efficacy vs Effectiveness) efficacy parameter. As a flexible pattern of meals and self-medication is warranted In table V [83][84][85][86][87] we have summarized the effects of repaglinide during this period, the use of a short-acting glucose-lowering drug on parameters of glucose metabolism as reported in observational such as repaglinide might offer some advantages. However, in studies.…”
Section: With Nph-insulin Vesp Plus Met Vs Biphasic 30/70 Human Insulmentioning
confidence: 99%